Recent advances in electrochemical biosensors for detection of oncoviruses - Goksu Ozcelikay; S. Irem Kaya; Ahmet Cetinkaya; Sibel A. Ozkan (Biosensors and Bioelectronics: X, 2022)
Oncoviruses are responsible for less than half of cancers in humans. In virus-related human oncogenesis, a multi-step process leads normal cells to transform into cancerous cells in the body. Among the various oncoviruses are human papillomavirus (HPV), Epstein-Barr virus (EBV), hepatitis B virus (HBV) and hepatitis C virus (HCV), human immunodeficiency virus (HIV), human herpesvirus (HHV-8), human lymphotropic virus-1 (HTLV-1), Merkel cell polyomavirus (MCV). The Pap smear test is critical in HPV screening, but its sensitivity is relatively low in cervical lesions, and the probability of giving false results is high. In this situation, create an alternative screening method. Therefore, the applied electroanalytical measurement techniques and electrode systems are important for detecting oncoviruses using electrochemical biosensors. Electrochemical sensor strategies such as genosensors, CRISPR-based recognition assay, aptamer-based biosensors, and immunosensors are used for the detection of oncoviruses. Major viruses causing cancer and oncovirus-related cancer types and electrochemical sensor strategies are described in the review. Studies that have been published in recent years are reported in tables for explaining details. This review considered the articles published in the last 10 years. The biosensor studies for cancer-causing viruses get gradually increased.